MICRO-STRUCTURAL OVERPRESSURE MECHANIZM AND THE ULTRA-HIGH PRESSURE METAMORPHIC ROCKS FORMATION - Wu H.L.; Chi S.L. (My University, 2003)
A new mechanism of micro-structural overpressure caused by the rock or mineral differences in structure and mechanical properties is applied to study the producing of ultra-high pressure metamorphic (UHPM) rocks and minerals. Using numerical simulated method we research some factors (rocks mechanical and thermal physical properties) that control the structural pressure and affect UHP metamorphic rock formation. The results show that the micro-structural pressure could play an important role to form UHP metamorphic rocks. The magnitude of micro- structural pressure between the rock's materials increases with some factors such as the differences in elastic modulus and thermal expansion coefficients, boundary pressure and temperature changes. In some conditions, for example, we suppose that the differences rate between the maximum elastic modulus and the minimum one in rocks or minerals is 5 times, it would cause the structural pressure of about 45 percent of the lithostatic pressure at the same depth. If the structural pressure due to the differences in the thermal expansion coefficients and the temperature changes are also added, on general conditions the total pressure at about 60km depth could meet the lower limited requirement of growth of coesite in ultra-high pressure rocks.